Unveiling Soil Salinity and Heavy Metal Patterns in the Khorat Plateau, Thailand: Implications for Sustainable Development Goals (SDGs) Monitoring (Indonesian Journal of Science and Technology, 2025)
Strongly saline soils cover approximately 2,400 km² of the Khorat Plateau, Thailand, posing challenges for agriculture and environmental sustainability. This study aimed to characterize soil salinity and heavy metal patterns across five soil layers in both badlands and paddy fields. Soil samples were analyzed for pH, electrical conductivity (EC), salt content, and concentrations of As, Cd, Cu, Fe, Mn, Pb, and Zn. Results showed higher EC and salt percentages in badlands, while paddy fields exhibited greater levels of micronutrient metals such as Cu, Fe, Mn, and Zn, likely due to agricultural practices. Heavy metal concentrations remained below national safety thresholds, suggesting low contamination risk. Statistical analyses revealed significant correlations among salinity indicators, soil properties, and metal contents. These findings provide baseline data critical for environmental monitoring and support Sustainable Development Goals (SDGs) 2 and 15 by informing strategies for food security, sustainable land use, and soil resource conservation in salinity-affected regions.
Keywords: Heavy metals; Khorat Plateau; Saline soil; Soil characteristics; Thailand